Sustainable Agriculture in Indonesia: A Review Article on Strategies, Challenges, and Opportunities from a Scientific Perspective - Apriyelita, Annisa; Marviano, Fajri Ramadhan (Jurnal Biologi Tropis, 2025)
Sustainable agriculture integrates ecological, social, and economic aspects to increase productivity without damaging the environment. This study aims to analyze the strategies, challenges, and opportunities for sustainable agriculture in Indonesia. The method used was a literature review of recent national and international journals with thematic analysis. The results indicate that effective strategies include crop diversification, agroforestry, organic fertilizers, biopesticides, water-efficient irrigation, and precision agriculture based on sensors and geospatial data. Key challenges include limited technology, capital, and policy support, while opportunities are driven by consumer awareness, supply chain digitization, and strengthening farmer institutions. In conclusion, the success of sustainable agriculture in Indonesia requires the integration of adaptive strategies, precision technology, and institutional support to strengthen food security and ecosystem sustainability.